FGFR1–ETV1–CXCL1 signaling in dermal fibroblast orchestrates fibroblast-associated itch - Zhen-Juan Zhong; Na Wei; Dong-Jin Li; Ting-Ting Shan; Ya-Ling Song; Xiao-Liang Wang; Si-Jia Zhao; Ya-Ping Liu; Xue-Feng Chen; Huan Wang; Yao-Qing Yu (Proceedings of the National Academy of Sciences, 2026)
Fibroblasts are a heterogeneous group of mesenchymal cells essential for tissue homeostasis maintenance and pathological responses. However, the mechanistic contributions of fibroblast plasticity to somatosensory dysfunction, particularly pathological pruritus, remain poorly characterized. Here, we developed fibroblast-associated itch models via acute incision and chronic bleomycin treatment. In Pdgfra CreER mice, chemogenetic activation of dermal fibroblasts using Gq-coupled designer receptors activated by designer drugs (DREADDs) evokes scratching behaviors, whereas inhibition with Gi-coupled DREADDs suppresses fibroblast-associated itch. Integrated in vitro and in vivo experimental evidence establishes a previously unrecognized pruritogenic signaling axis centered on fibroblast growth factor receptor 1 (FGFR1), transcription factor ETS variant 1 (ETV1), and chemokine ligand 1 (CXCL1) in fibroblast-associated itch. Moreover, ETV1 nuclear translocation during dermal fibroblast activation is coordinated by the enzyme poly-ADP-ribose polymerase 1. Finally, conditional knockout of ETV1 in Pdgfra CreER ;ETV1 flox mice verify the essential role of the signaling in fibroblast-associated itch. Collectively, FGFR1–ETV1–CXCL1 axis in dermal fibroblasts functions as a pivotal itch signaling, establishing a conceptual framework that links fibroblast dynamics to somatosensory disorders.